2001
DOI: 10.1002/path.829
|View full text |Cite
|
Sign up to set email alerts
|

Early distant relapse in ?node-negative? breast cancer patients is not predicted by occult axillary lymph node metastases, but by the features of the primary tumour

Abstract: Early distant relapse occurs in a minority of node-negative breast cancer patients. Whether this poor prognosis can be predicted by the features of the primary tumour, or by the presence of occult metastases in the "negative" lymph nodes (LNs), remains a matter of debate. One hundred and four T(1-2)N(0)M(0) breast carcinoma patients were divided into two groups: group 1 (44%) showing early distant relapse with a median disease-free survival of 25 months, and group 2 (56%) showing no evidence of disease after a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
66
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(76 citation statements)
references
References 38 publications
9
66
1
Order By: Relevance
“…Large central necrosis or fibrosis have also been reported to correlate with poor prognosis in early breast cancer [43], and to be strongly associated with basal-like [44] and ER-negative breast cancer [45]. Information on their prognostic value within the subgroup of triple-negative IDC is, however, lacking.…”
Section: Discussionmentioning
confidence: 99%
“…Large central necrosis or fibrosis have also been reported to correlate with poor prognosis in early breast cancer [43], and to be strongly associated with basal-like [44] and ER-negative breast cancer [45]. Information on their prognostic value within the subgroup of triple-negative IDC is, however, lacking.…”
Section: Discussionmentioning
confidence: 99%
“…2 However, the biologic potential of a tumor may also depend on other factors, including primary tumor size/volume, histologic and nuclear grades, lymphovascular invasion, and tumor necrosis/fibrosis. 4 All these features may in some way work to enhance partially or prominently the ability of a neoplasm to survive and proliferate at a secondary site. For these reasons, we have come to appreciate the need for accurate, consistent pathologic assessment of tumor size, histologic and nuclear grade, stromal angiogenesis, and local as well as distant metastais.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have suggested that histologic grade and, sometimes, the size of the tumor predict more accurately disease recurrence. 4 Although these findings are more applicable to invasive carcinomas, it has long been known that certain types and higher grades of DCIS have a greater propensity for disease recurrence. 2 The current study supports the findings of earlier studies that concluded that microscopic tumor deposition does not have significant clinical implications, especially if visualized by IHC only.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations